2007
DOI: 10.1111/j.1467-8691.2007.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Convergence or National Specificity? Testing the CI Maturity Model across Multiple Countries

Abstract: This study empirically tests the Continuous Improvement (CI) maturity model across multiple countries. The analysis is based on data from the 2nd International CINet Survey, limited to the situation in Australia, Italy, the Netherlands, Spain, Sweden and the United Kingdom. Despite some differences in Continuous Improvement maturity level between countries, findings lend support to the convergence argument. Regardless of national specificity, Continuous Improvement behaviour patterns emerge in a similar fashio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In a later study using survey data from 452 European and Australian manufacturing companies, Dabhilkar et al (2007) remarkably found no significant differences in the relative 217 Implementing lean practices importance of improvement routines for operational performance, neither within nor across countries. A possible explanation is that they analysed this relationship using a regular regression.…”
Section: Importance Of Individual Improvement Routinesmentioning
confidence: 91%
See 3 more Smart Citations
“…In a later study using survey data from 452 European and Australian manufacturing companies, Dabhilkar et al (2007) remarkably found no significant differences in the relative 217 Implementing lean practices importance of improvement routines for operational performance, neither within nor across countries. A possible explanation is that they analysed this relationship using a regular regression.…”
Section: Importance Of Individual Improvement Routinesmentioning
confidence: 91%
“…This study was based on a Dutch sample and small set of cases, which does not allow for generalisation to other contexts and types of companies. Although Dabhilkar et al (2007) found no national differences amongst the relationships between improvement routines and operational performance, this study took a novel approach. Future research should replicate this approach and study improvement routines as necessary conditions in different countries and industries, and/or use suitable samples to test the propositions developed in this study.…”
Section: Recommendations For Future Researchmentioning
confidence: 92%
See 2 more Smart Citations
“…Construct definitions and labels assigned to scales guided but did not dictate categorisation because labels were highly varied and often not a good indicator of instrument content ( e . g ., authors used the following construct labels for very similar measures of QI climate: organizational culture that supports QI [56], organizational commitment to QI [57], QI implementation [58], degree of CQI maturity [59], quality management orientation [60], and continuous improvement capability [61]). Instrument content was summarised in separate tables for each of the content domains from the InQuIRe framework: (1) CQI implementation and use, (2) organizational context, and (3) individual level factors.…”
Section: Methodsmentioning
confidence: 99%